2012
DOI: 10.1007/s00441-012-1440-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular mechanisms underlying the role of blood vessels in spinal cord injury and repair

Abstract: Spinal cord injury causes immediate damage of nervous tissue accompanied by the loss of motor and sensory function. The limited self-repair ability of damaged nervous tissue underlies the need for reparative interventions to restore function after spinal cord injury. Blood vessels play a crucial role in spinal cord injury and repair. Injury-induced loss of local blood vessels and a compromised blood-brain barrier contribute to inflammation and ischemia and thus to the overall damage to the nervous tissue of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
101
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 185 publications
(220 reference statements)
0
101
0
1
Order By: Relevance
“…TJs are located at the apical end of the interendothelial space and are connected to adherens junctions near the basal end of the inter-endothelial space (23). TJ proteins, such as transmembrane proteins claudin-5 and the peripheral membrane protein ZO-1, are essential to the normal functioning of TJs (24).…”
Section: Discussionmentioning
confidence: 99%
“…TJs are located at the apical end of the interendothelial space and are connected to adherens junctions near the basal end of the inter-endothelial space (23). TJ proteins, such as transmembrane proteins claudin-5 and the peripheral membrane protein ZO-1, are essential to the normal functioning of TJs (24).…”
Section: Discussionmentioning
confidence: 99%
“…31 This exacerbates the initial injury because the bloodborne species that enter the spinal cord parenchyma are toxic to neural cells and because the progressive and expanding vascular destruction leads to secondary perilesional ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that angiogenesis plays a very important role in axonal regeneration after spinal cord injury. In addition to relying on nerve fiber regeneration and synaptic reconstruction, tissue repair and functional recovery after spinal cord injury require nutritional support provided by blood vessels to nourish damaged tissues (Oudega, 2012). Promoting the formation of blood vessels near the site of injury and providing the environment necessary for cell survival may promote axonal regeneration, thereby improving treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Damaged nerve tissues have a very limited ability to self-repair, requiring necessary external intervention to restore lost function due to spinal cord injury (Oudega, 2012). Recent studies have indicated that angiogenesis plays a vital role in spinal cord injury repair (Reginato et al, 2011).…”
Section: Introductionmentioning
confidence: 99%